21st Report of Session 2019-21 : Drawn to the special attention of the House : Draft Enterprise Act 2002 (Share of Supply) (Amendment) Order 2020 ; Enterprise Act 2002 (Specification of Additional Section 58 Consideration) Order 2020 ; Town and Country Planning (Permitted Development and Miscellaneous Amendments) (England) (Coronavirus) Regulations 2020 /: Drawn to the special attention of the House : Draft Enterprise Act 2002 (Share of Supply) (Amendment) Order 2020 ; Enterprise Act 2002 (Specification of Additional Section 58 Consideration) Order 2020 ; Town and Country Planning (Permitted Development and Miscellaneous Amendments) (England) (Coronavirus) Regulations 2020. ([2020-07-09]) - Unknown
No abstract available